Correlação entre o fator de refletividade do radar e a vazão no rio Mundaú - Barros, Adriano Aubert Silva (2011)
This application aims to identify a possible correlation between the reflectivity factor signal RADAR Weather Radar System of Alagoas (SIRMAL), with the flow of the Rio Mundaú, data obtained fromthe Hydrological Station National Water Agency (ANA) in BoaFortuna, Rio Largo, Alagoas. What is required is a remote monitoring and continuous rate of flow, at one point the river basin Mundaú in order to predict possible flood waves. The floods in the river Mundaú are recurrent, having brought great losses in material resources and human lives for decades, their monitoring is of fundamental importance for better planning and management of these resources. For this we constructed a computer code in object-oriented language, Object Pascal. The program reads the image in jpeg format, generated and provided by SIRMAL on his Internet site, spatially integrates all the values of reflectivity of the microwave pulse on the watershed, determining the volume and then precipitated considered high rainfall area on the Watershed River Mundaú. This value is associated with the reflective state of the basin, at a given time, indicates the amount of precipitated water in the basin for a given period. The high rainfall is related to precipitation over the basin and consequently the flow in river. To verify the correlation with the flow, were chosen five months, the period from 2004 to 2006, when the flow measured at the farm Good Fortune, showed abrupt changes and sought similar variations in rainfall height, measured from the image processing radar. For the months of January 2004, December 2005 and September 2006, we obtained a correlation exceeding 70% between the reflectivity factor and the flow. From the daily analysis of the height and flow rate determined to be a qualitative correlation. This was obtained from the flow data, derived from stories of the season series, obtained in the HIDROWEB ANA rainfall and the height obtained with the method. The correlation was promising but not conclusive. Through the analysis it was demonstrated that the sensitivity of variations in height, indicating up to 24 hours to raise the level of flow to 60% of cases.